Kedudukan Hukum Adat Duan Lolat Terhadap Penyelesaian Delik Dalam Criminal Justice System - Yeheskel Wessy (LUTUR Law Journal, 2022)
The State of Indonesia is a State of Law (rechtstaat/staats law), which completely separates positive law (positivism law) from customary law (adatrecht) as unwritten law (custom), so that when a criminal act/criminal action occurs (delict) the state with all its powers according to the law (formal criminal law and material criminal law) through the related judiciary (sub system) acts to defend state law in order to protect the interests of the injured legal subject (victim). The results show that the system and values ​​and laws of the Duan-Lolat customary law have a position in national law as a sub-system of the Indonesian customary law system so that Duan-Lolat customary law gets its position in the criminal justice system without invalidating the national law in this case. material criminal law and the ideal form of criminal justice system in accommodating Duan-Lolat customary law against the settlement of offenses at the pre-adjudication and adjudication stages carried out by the authorized sub-system as a component of criminal justice.